Bilateral talus neck fracture in an 11-year-old patient resulting from a fall from height: A case report - Tekşan, Emre; Karadeniz, Sercan (Journal of Surgery and Medicine, 2022)
We here present an 11-year-old patient with bilateral Hawkins type 3 talus neck fractures resulting from a fall from height. When the patient was brought to the Emergency Department, the ankles were edematous and there were bilateral talus neck fractures with subtalar dislocation. The taluses on both sides were entered with anteromedial and anterolateral incisions, and after an open reduction, the fractures were fixed with one cannulated screw from the anterior and one from the posterior side. No additional edema developed. The patient was followed up for 2 days in the ward, then discharged with outpatient follow up recommendations. Pediatric bilateral talus neck fractures are rare and must be treated immediately.